2020
DOI: 10.3389/fpsyg.2020.01939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Picture-Book Reading With Additive Audio on Bilingual Preschoolers’ Prefrontal Activation: A Naturalistic Functional Near-Infrared Spectroscopy Study

Abstract: Acquiring a second language (L2) has the power to shape cognition and even the function and structure of the brain. Picture-book reading with additive audio (PRA) is a popular and convenient means of providing L2 exposure for non-balanced bilingual children; however, its contribution to bilingual children's brain activity is unclear. This study conducted a rigorous bilingual word comprehension experiment and a naturalistic PRA task to explore the effect of L2 processing on brain activation among English as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 106 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…However, clustering co‐occurrences of words and how they relate provided the possibility to predict the newest tendencies and the future of fNIRS. For example, in the last year, authors dedicated their attention to cognitive functions and motor impairment, 56,58,122,123 development and language, 124–127 social and emotional engagement, 128–130 BCI systems, 63,64 and rehabilitation 131 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clustering co‐occurrences of words and how they relate provided the possibility to predict the newest tendencies and the future of fNIRS. For example, in the last year, authors dedicated their attention to cognitive functions and motor impairment, 56,58,122,123 development and language, 124–127 social and emotional engagement, 128–130 BCI systems, 63,64 and rehabilitation 131 …”
Section: Discussionmentioning
confidence: 99%
“…For example, in the last year, authors dedicated their attention to cognitive functions and motor impairment, 56,58,122,123 development and language, [124][125][126][127] social and emotional engagement, [128][129][130] BCI systems, 63,64 and rehabilitation. 131 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of natural functional near-infrared spectroscopy that explored the effects of audio picture book reading on prefrontal cortex activation in bilingual preschool children, the study showed that under the condition of picture book Reading plus English audio, cognitive control, and Language processing in early bilinguals were significantly improved. The effect of prefrontal cortex activity is more active (Li, Ding, et al, 2020). When the picture book story was presented to the children in the form of sound stimulation, the magnet-electroencephalographic (MEG) experimental data was analyzed according to the schema theory.…”
Section: Audio Picture Book Interventionmentioning
confidence: 99%
“…However, despite well-designed longitudinal studies of infant and brain function studies in adults, very little research has been conducted to examine neural correlates of joint attention in preschool children, especially in left-behind groups. Consequently, due to its safety, portability, relatively high temporal resolution, and insensitivity to head movement, we recruited fNIRS for the joint attention task in the current study to evaluate the effect of joint attention on prefrontal activation in left-behind children [20].…”
Section: Introductionmentioning
confidence: 99%